Peripheral T-cell Lymphomas - Pier Paolo Piccaluga (IntechOpen, 2019)
In this book the reader will find a collection of chapters written by different research teams describing different aspects of peripheral T-cell lymphoma pathobiology, classification, and treatment. This work is mainly addressed to researchers already working in this area, but it is also accessible to anyone with a scientific background who desires to have an updated overview of the recent progress in this domain. It will also be valuable to scientists and physicians who have become newly involved in this field. Each chapter is self-contained and can be read independently of the others. This book intends to provide highlights of the current research as well as the current gold standards for diagnosis and treatment of these diseases, showing the recent advances in the personalized approach to T-cell derived lymphomas.
English
Keywords: Medicine; Hemato-Oncology; Oncology; Health Sciences